PENERAPAN PERAWATAN KOREKTIF PADA KASUS KERUSAKAN SLOTTING ATTACHMENT MESIN FRAIS - Aldo Welihardo; Adi Saputra; Feriadi, Indra; Tuparjono (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2024)
The final project aims to restore the function of the slotting attachment of the milling machine in the Bangka Belitung State Polman laboratory workshop which was damaged. The repair of the slotting attachment aims to optimize the performance of the slotting so that it can operate normally. The slotting repair process on the milling machine begins with identifying and analyzing the damage using the method 5 whys analysis. The damage found was damage to the slotting component, damage to the eccentric shaft, damage to the bushing, bushing. The repair process carried out was to replace damaged and worn components. From the results of the repair, the slotting attachment was able to function properly again.